Teaching Phonetics and Pronunciation in ELT; How Important and Which One to be Taught? - Himmayati, Itsna Millatul; Triyoko, Hanung (UNDIKMA, 2024)
There are several branches of linguistics, one of them is phonetics. Phonetics is one of the most important parts of linguistics in learning a language, especially in speaking skill. This article explores the significance of teaching phonetics and pronunciation in English language teaching (ELT). This article use literature review as the method of research. This research delves into the reasons why these aspects are crucial for effective communication and language acquisition. The article provides insights into the most effective methods and strategies for teaching these skills, including drill method, audio lingual method (ALM) and realia. Moreover, phonetic training; reading aloud; listening and repeating; rhymes and verses; rules and instructions; awareness-raising activities; spelling and dictation and ear training also can be used in teaching phonetics and pronunciation.Ultimately, the article aims to highlight the importance of incorporating phonetics and pronunciation instruction into ELT programs to ensure that learners develop accurate and fluent speaking skills.